The Role of Marketing Strategy, Program Innovation, and Social Media in Increasing Student Registration Interest at PAUD Tiara Sani - Wahyuni, Pertiwi; Zulistiani (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the role of marketing strategies, program innovations, and social media in increasing interest in enrolling in PAUD Tiara Sani. Using a qualitative approach with case study analysis, this study explores how these three factors collaborate in attracting public attention. The results of the study indicate that PAUD Tiara Sani actively promotes the school through word of mouth and social media, with one of the leading promotional methods being an open house that allows parents to interact directly with the school. In addition, innovations in creative programs, such as making batik using leaves and parenting activities and outings class , is a special attraction for parents. Marketing documentation carried out on social media displays content that is relevant to children's learning activities, school events, and testimonials from alumni and parents. However, the limited number of social media followers is one of the challenges, and further research is expected to explore the effectiveness of paid advertising and collaboration with local communities to expand the reach of promotions. This study provides important insights into the application of marketing strategies in the digital era to increase student registration interest.